True blue - CLEGG, Susan; CUNDY, Andrew; HOLTER, Jennifer; DADSWELL, Christopher (Current Archaeology, 2010)
The authors have used geochemical techniques to identify a blue pigment on a fragment of wall-plaster from room 55 of the Fishbourne Roman villa; it was derived from lapis lazuli rather than the more normal blue frit.
p. 42-43.
Keywords: Études techniques; Analyse chimique; Analyse chromatique; Bleu; Enduit pariétal; Lapis lazuli; Pigment; Villa (Fishbourne, GBR); Analyse géo-physique; Fishbourne; Grande-Bretagne